Nurturing children's religious values in the social education environment In Makassar city - Muslimin, Abdul Azis; Haeriyyah; Muhyiddin; Sitti Muthmainnah; Nurhilaliyah (Indonesian Journal of Islamic Religious Education, 2024)
Education is a process that will be largely determined by three factors, namely: first, the family environment, where parents are the determining factor in the formation of children's attitudes and behavior, second, the school environment, where teachers play a very important role in the cognitive formation of students and third is the community environment, so that this environment becomes a free medium of interaction between children/students from the previous two environments. By using qualitative research, this research focuses on the development of religious values and the formation of social values. The results of this study reveal that the concept of halalan tayyibah as an initial provision to the family in the family as an initial coaching place. Emphasizing the importance of education as a holistic process influenced by three primary environments. Firstly, the family environment, where parents play a crucial role in shaping children's attitudes and behaviors. Secondly, the school environment, where teachers are instrumental in the cognitive development of students. Thirdly, the community environment, which provides a broader context for social interaction, integrating influences from both the family and school.